OVOMUCOID (THE MOST IMPORTANT EGG WHITE ALLERGEN) AS A CAUSE OF SEVERE EGG ALLERGY:A REVIEW - Ahmed Taha; Ayaz Hafsa; Nisar Dua; Moin Areeba (Sanamed, 2024)
Hypersensitivity, or an allergy to highly valuable chicken egg proteins, is a prevalent symptomatic condition. It occurs when the immune system of a hypersensitive or allergic individual overreacts upon contact with egg allergens (egg proteins), triggering a complex immune response. Among these allergens, ovomucoid is the most allergenic, making up 11% of egg white. Ovomucoid is both thermostable and resistant to digestion, distinguishing it from other egg white proteins. While ovalbumin is the most abundant protein in egg white, ovomucoid is responsible for the majority of its allergic properties. Humans generally lack tolerance to both raw and cooked eggs due to the presence of this allergenic protein.